EFEITO INSETICIDA DE ALGUNS EXTRATOS VEGETAIS SOBRE A MOSCA-DO-MEDITERRÂNEO EM LABORATÓRIO - Potenza, Marcos Roberto; Bergmann, Eliana Cherubini; Nishimori, Regina Kazue; Benedicto, Luci Hessel (REVISTA DE AGRICULTURA, 2015)
EFEITO INSETICIDA DE ALGUNS EXTRATOS VEGETAIS SOBRE A MOSCA-DO-MEDITERRÂNEO EM LABORATÓRIO